Healthcare systems and health economics in GCC countries: informing decision-makers from the perspective of the Gulf health economics association - Yazed AlRuthia; Sara Aldallal; Hana A. Al-Abdulkarim; Hana A. Al-Abdulkarim; Ahmed Al-jedai; Ahmed Al-jedai; Hajer Almudaiheem; Anas Hamad; Anas Hamad; Khalifa Elmusharaf; Mouza Saadi; Hamda Al Awar; et al. (Frontiers in Public Health)
Following the discovery of oil, citizens of the Cooperation Council for the Arab States of the Gulf (GCC), which includes Bahrain, Kuwait, Qatar, Oman, the United Arab Emirates, and Saudi Arabia, have enjoyed the benefits of universal healthcare. However, as the population and healthcare demands in the GCC continue to grow, financing these healthcare systems without adequately considering the value of reimbursed health technologies and the effectiveness of various policies has become increasingly challenging. While numerous narrative reviews and government reports have discussed the healthcare systems in these nations, they have not sufficiently addressed the approval processes, economic evaluations, and reimbursement mechanisms for health technologies. In response to this gap, experts in health economics and outcomes research (HEOR) from the Gulf Health Economics Association – recognized as key opinion leaders in public health and academia across the six GCC countries – conducted a focus group discussion. This focus group meeting, which was recorded and transcribed verbatim to be later thematically analyzed, aimed to characterize the current state of healthcare systems within the GCC, identify challenges in adopting and implementing health economic evaluations to inform policymakers and propose recommendations to expedite the integration of HEOR in the assessment of various health policies and technologies within their respective countries. The convened experts also underscored the importance of collaboration among GCC member states to enhance the adoption of robust health technology evaluations and improve patient access to cost-effective treatments.